Bottom-up and top-down factors influencing consumer responses to food labels: a scoping review of eye-tracking studies - Migena Proi; Emilia Cubero-Dudinskaya; Danilo Gambelli; Simona Naspetti; Raffaele Zanoli (Agricultural and Food Economics)
Abstract Eye-tracking technology has become vital for exploring consumers’ preferences for food labels. This paper carried out a scoping literature review to comprehensively summarize the main findings in the food labelling research from 1999 to 2023. We selected 52 studies conducted using eye tracking for the analysis of consumers reactions to food labels. In particular, the review focuses on the role that bottom-up factors and top-down factors may have on consumers’ visual attention. The results show that consumers’ visual responses are influenced by both top-down and bottom-up factors but often rely on heuristics to reduce cognitive load. Simple formats like color-coded labels, labeling claims, or signs are generally preferred. Consumers tend to use these shortcuts particularly for health-oriented choices or due to time-constrains. The role of certification schemes and sustainability claims seem to be not fully considered in the reviewed research and may be worth further investigation.